Views regarding methodology of contemporary European studies - Grigore VASILESCU; Cristina MORARI (Eastern European Journal of Regional Studies, 2015)
The article analyzes some very important questions of contemporary European Studies, such as actually situation, problems existing in this domain, the specific of European Studies methodology from the multidisciplinary, interdisciplinary and transdisciplinary points of views. A particular attention is paid towards the systematization, classification and analysis of the most important European Studies methods, inclusively generally, particularly and specific ones. Also, a special reference is made to the present necessities and perspectives of the future development of the European Studies methodology. In this way, there are identified a range of problems that face European Studies methodology. Through them is underlined the weakness of European Studies methodology as it is a very young domain. Another problem is the controversy of the issue, because there are a lot of visions and opinions regarding the status of European Studies methodology. The existing problems in the domain of European Studies methodology can be explained by the fact that European Studies and especially some of its compartments as Political European Studies had developed their own methodologies recently. That is why, their methodology is not yet recognized by the all researchers in domain and thus it is not transferred to students and young researchers through methodology teaching… .